Respecting Symptoms in Thoracic Aortic Aneurysm Management: A Case of Symptomatic Necrotizing Granulomatous Aortitis - Kuzmik, Gregory A.; Sang, Adam X.; Cai, Guoping; Tranquilli, Maryann; Elefteriades, John A. (International Journal of Angiology, 2012)
A 41-year-old woman presented with chest pain of unclear etiology in the setting of a mildly dilated ascending aorta. Computed tomography angiography showed an aorta with an irregular contour and an aneurysm of 4.5 cm. There was no radiographic evidence of rupture or dissection. The patient was taken to the operating room and was found to have severe aortitis with marked localized wall thinning at imminent risk of aortic rupture. Aortic pathology demonstrated necrotizing granulomas of noninfectious etiology. This case illustrates the importance of respecting symptoms in surgical decision making for thoracic aortic aneurysms that may not meet standard interventional criteria.
Keywords: aortic aneurysm; aortic operation; aortic pathology